Forecasting river flow in the USA: a comparison between auto-regression and neural network non-parametric models - Baareh, Abdel Karim M.; Sheta, Alaa F.; Khnaifes, Khaled Al (Proceedings of the 6th WSEAS International Conference on Simulation, Modelling and Optimization, 2006)
Keywords: dept.csc; ⛔ No DOI found

Data, Network, and Internet Communications Technology - Elahi, Ata; Elahi, Mehran (Thomson Delmar Learning, 2006)
"This thorough primer examines the technological aspects of networking through a practical approach. Readers will gain knowledge of local area networks (LANs), wide area networks (WANs), the Internet, wireless LANs, wireless MANs, voice over IP (VoIP), as well as asynchronous transfer mode (ATM) and network security. Introductory chapters on foundational topics, such as data communications and computer architecture give readers the knowledge base they need to understand more complex networking concepts. This book effectively utilizes a practical approach to networking rather than a strict focus on theory or math, and requires no prior background in communications technology."–BOOK JACKET.
Keywords: Computer networks; Textbooks; Textbooks; Data transmission systems; dept.csc; faculty_collection

Creating interactive maps using Flash - Workman, Russell W. (Current Developments in Technology -Assisted Education, 2006)
Citation Key Alias: pop00424
Keywords: dept.csc; ⛔ No DOI found

Performance-based modeling and restructuring of object oriented software for pipeline architecture - Abdel-Raouf, Amal; Ammar, Reda A; Fergany, Tahany A (Computer Science and Software Engineering, 2006)
Pipelining is the suitable architecture to adopt applications that are naturally divided into stages. Recently, applications tend to be Object Oriented (OO). Within the context of OO, there are a lot of interactions among different objects that result in many communication activities. Besides the feed-forward communication activities, many bypassing activities are generated in the pipeline structure. In this paper, we present a performance model that analyzes and evaluates the execution and communication times of OO software that runs on pipeline architecture. The model realizes both the feed-forward and the bypassing communication. We utilize the model to restructure the target software to achieve better performance. The restructuring algorithm has two phases; the first phase is concerned with maximizing the throughput. The second phase aims to minimize the latency and fully exploit the system resources. © 2006 - IOS Press and the authors. All rights reserved.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Communication activities; Distributed systems; Feed-forward communication; Object oriented programming; Object oriented software; Performance modeling and analysis; Performance-based models; Pipeline architecture; Pipelines; Restructuring algorithms; dept.csc; distributed systems; object-oriented software; pipeline architecture; software restructuring

COinS for the link trail - Chudnov, Daniel (Library Journal, 2006)
tex.unique-id: ISI:000239013700003
Keywords: dept.csc; ⛔ No DOI found

Quantitative confirmation of visual improvements to micro-CT bone density images - Daponte, John S; Clark, Michael R; Nelson, Paul; Sadowski, Thomas; Wood, Elizabeth (Visual Information Processing Conference, 2006)
The primary goal of this research was to investigate the ability of quantitative variables to confirm qualitative improvements of the deconvolution algorithm as a preprocessing step in evaluating micro CT bone density images. The analysis of these types of images is important because they are necessary to evaluate various countermeasures used to reduce or potentially reverse bone loss experienced by some astronauts when exposed to extended weightlessness during space travel. Nine low resolution (17.5 microns) CT bone density image sequences, ranging from between 85 to 88 images per sequence, were processed with three preprocessing treatment groups consisting of no preprocessing, preprocessing with a deconvolution algorithm and preprocessing with a Gaussian filter. The quantitative parameters investigated consisted of Bone Volume to Total Volume Ratio, the Structured Model Index, Fractal Dimension, Bone Area Ratio, Bone Thickness Ratio, Euler's Number and the Measure of Enhancement. Trends found in these quantitative variables appear to corroborate the visual improvements observed in the past and suggest which quantitative parameters may be capable of distinguishing between groups that experience bone loss and others that do not.
1 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Algorithms; Bone Thickness Ratio; Computerized tomography; Digital filters; Euler's Number; Gaussian filters; Image enhancement; Image sequences; Medical imaging; Optical resolving power; dept.csc; dept.phy

Animating climate model data - Daponte, John S; Sadowski, Thomas; Thomas, Paul (Visual Information Processing Conference, 2006)
This paper describes a collaborative project conducted by the Computer Science Department at Southern Connecticut State University and NASA's Goddard Institute for Space Science (GISS). Animations of output from a climate simulation math model used at GISS to predict rainfall and circulation have been produced for West Africa from June to September 2002. These early results have assisted scientists at GISS in evaluating the accuracy of the RM3 climate model when compared to similar results obtained from satellite imagery. The results presented below will be refined to better meet the needs of GISS scientists and will be expanded to cover other geographic regions for a variety of time frames.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Animation; Climate model data; Computer simulation; Data reduction; Geographical regions; Imaging systems; Mathematical models; Satellite imagery; Satellites; Simulation math model; dept.csc; dept.phy

Geospatial visualization of student population using Google™ Maps - Podnar, Hrvoje; Gschwender, Adam; Workman, Robert; Chan, Jian (Journal of Computing Sciences in Colleges, 2006)
Citation Key Alias: lens.org/159-954-829-997-02X tex.type: [object Object]
Keywords: dept.csc; ⛔ No DOI found